2022
DOI: 10.1111/capa.12450
|View full text |Cite
|
Sign up to set email alerts
|

Lopsided lobbying? Regulatory opportunism and the Office of the Commissioner of Lobbying

Abstract: This article traces the institutional trajectory of the Office of the Commissioner of Lobbying (OCL). It is argued that political elites' electoral prioritization, foremost demonstrated within the Lobbying Act, has undermined the OCL in its mission toward a balanced and transparent lobbying system. Politicians have demonstrated a form of regulatory opportunism in which change is filtered by electoral calculations. Gaps in the Commissioner's authority, the registration floor, and the scope of communication repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 79 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…The Quebec lobbying legislation is less stringent than the Canadian one (Chari et al, 2007), which has recently been described as limited (Fry, 2022). Quebec, too, is marked by a lack of political interest in fundamental reform.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Quebec lobbying legislation is less stringent than the Canadian one (Chari et al, 2007), which has recently been described as limited (Fry, 2022). Quebec, too, is marked by a lack of political interest in fundamental reform.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the chronology of events, as well as a content analysis of a parliamentary debate about this issue, unequivocally showed that this change was not the result of an attempt to respond to a scandal (Holman & Luneburg, 2012; Ozymy, 2010) or a desire for cross‐jurisdictional learning by the government (Crepaz, 2017; Pross & Shepherd, 2017). Nor does the change appear to have been driven by electoral calculations (i.e., the mechanism of regulatory opportunism) (Fry, 2022) since it occurred serendipitously more than a year after the provincial election and not due to an explicit electoral pledge. Indeed, these mechanisms do not seem to account for the action of political actors in the case under study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Canadian federal government tested its procurement agility during the pandemic. The We Charity scandal is an example of this challenge (see Fry, 2022). …”
mentioning
confidence: 99%